Stalin's quest for gold : the Torgsin hard-currency shops and Soviet industrialization - Osokina, E. A. (Elena Aleksandrovna) (Cornell University Press, 2021)
"State-run stores called Torgsin (1930-1936), which exchanged food and goods for people's heirlooms during the mass famine in the USSR, became a major means to pay the tremendous foreign debts acquired from purchasing foreign equipment and technologies"--